Servant and transformational leadership: a supply chain management perspective - Nichols, Thomas; D Anderson, Trisha; Erakovich, Rod (Journal of Management and Science, 2020)
We examine the association between leadership style (transformational and servant) and the type of supply chain (efficient or responsive) and the impact of employee engagement on customer satisfaction. We propose a model for examining the influence of transformational and servant leadership on the efficient and responsive type supply chains. We present 7 propositions and present a novel view of leadership by viewing it through the lens of contextual leadership theory in which the context is defined by the type of supply chain, effective or responsive. While both transformational and servant leadership are viewed as positive, even normative, forms of leadership, we have found that the efficacy of each type of leadership can be influenced by the context in which they operate and especially in supply chain environments.